Evaluating Blue Economy Dynamics Through the Influence of Marine Fuel Price Fluctuations on the Purchasing Power and Socioeconomic Welfare of Indonesian Captured Fisheries - Sri Endang Kornita; Ufira Isbah; Indah Rodianawati (Agriculture Journal, 2026)
The capture fisheries sector is a key pillar of Indonesia’s blue economy and food security, yet it remains highly sensitive to fluctuations in marine fuel prices. This study applies a mixed-method approach—combining monthly time-series data (2019–2023) with field interviews in Pati and Indramayu—to assess how fuel price changes affect fishers’ purchasing power and socioeconomic welfare. Results show that fuel accounts for 60–70% of operational costs, and the 2022 price surge triggered widespread fishing stoppages that disrupted coastal economies; around 70% of fishers in Pati became inactive, while large vessels in Indramayu had already ceased operations earlier. The Fishermen’s Terms of Trade (FiTT) declined from 106.45 in 2022 to 101.76 in 2024, indicating a continued erosion of welfare. Regression analysis confirms that rising non-subsidized fuel prices significantly reduce net income, while subsidy access has a positive effect, although only about 30% of small-scale fishers benefit from it. The study also highlights increasing financial pressure and reliance on informal lending, underscoring the need for targeted fuel price stabilization, improved digital subsidy distribution, accelerated adoption of alternative energy, and more comprehensive welfare indicators.